Agricultural contaminants in the production of Corn Zea mays L. choclero variety in Curahuasi Apurímac, Peru - Barreto_Carbajal, Juan S. (2022)
The objective of the research was to describe the use of pollutants in the cultivation of Maize Zea mays L. The study was carried out in the district of Curahuasi, Abancay Apurímac Province, Peru. The type of study was quantitative with an explanatory level. The Concacha-Curahuasi transect was evaluated, simple random probabilistic sampling was applied in a total population of 345 families from the communities and producer associations, the sample was 20% of farmers. The field work was carried out in October 2018. The results achieved showed that 92.16% of farmers use insecticides indiscriminately to control the aforementioned pests, 94.1% consider that corn, water and soil are contaminated. They do not do any treatment for the final disposal of empty containers. In conclusion, in the production of choclero corn, in Curahuasi, they use agrochemicals that contaminate the crops and the environment.